The Prevalence of Amputation in Regional Asia due to Diabetic Foot Ulcers 2024: A Systematic Review and Meta-analysis - Athena, Aegle; Susanti, Indah; Auron, Afrodita; Atfat Malic, Rohan; Burhan, Asmat; Kumar, Vijay (Global Indonesia Health Care (GOICARE), 2024)
Background: Over the past decade, the prevalence of diabetic foot ulcers (DFUs) has notably increased, posing a significant risk of foot amputation in individuals with diabetes. Purpose: This systematic review and meta-analysis aimed to determine the rates of amputation associated with DFUs in patients with diabetes mellitus. Methods: A comprehensive literature search was conducted across multiple databases, including Scopus, PubMed, Cochrane, Web of Science, DOAJ, and Google Scholar. Full-text articles related to diabetic foot ulcer amputation were reviewed and extracted for analysis. Publication Bias: Assessed using a funnel plot in Jamovi (2.0.0), indicating a likelihood of publication bias. Meta-analysis Summary: Conducted using the Joanna Briggs Institute methodology, yielding a pooled meta-analysis result of 0.027. Odds Ratio (OR): Calculated for amputation risk in DFU patients, with a 95% Confidence Interval (CI). Random Effects Model: Employed to synthesize relevant outcomes. Heterogeneity: Evaluated using the I² statistic. Forest Plots: Generated to visualize study results. Results: Eighteen studies were included in the meta-analysis, encompassing a total of 7115 DFU patients in the Asian region. Among these patients, 2730 underwent foot amputations. Amputation Rate: The incidence of foot amputation was significantly higher among DFU patients. Pooled Odds Ratio: The OR for foot amputation in DFU patients was 0.34 (95% CI: 0.23-0.46). Publication Bias: The asymmetrical funnel plot suggested a high likelihood of publication bias. Conclusion: The presence of DFUs significantly elevates the risk of foot amputation in diabetic patients. Continuous monitoring and preventive strategies are essential to mitigate this risk, particularly in the Asian population.